Behavioral-Based Safety Leadership's Impact on Organizational Safety Culture and Incident Causation in the High-Risk Maritime Environment - Manjarres-Wahlberg, Calvin Jordan (Digital Repository of Theses, 2024)
The impact of behavioural-based safety leadership on organisational safety culture and incident causation within the high-risk maritime environment has been researched in detail in this dissertation. The research discusses the hazards, risks and challenges associated with living and working at sea within the dynamic naval and merchant navy environments. The study explored the critical factors of leadership in shaping positive safety behaviours and the impact behavioural-based safety leadership has on reducing incident causation. The research is grounded in a comprehensive review of existing academic and grey literature, which establishes a theoretical foundation encompassing safety leadership theories, organisational safety culture, and incident causation models. This background provides a context for understanding the complex link between leadership behaviours and safety outcomes within the high-risk maritime environment. The research uses a mixed-methods approach, combining quantitative data from surveys with maritime professionals and qualitative insights from case studies and interviews. This triangulation methodology provides a detailed investigation into the relationship between safety leadership behaviours, organisational safety culture and incident causation. Key findings include the identification of specific antecedents and leadership behaviours that positively influence safety culture including, gender diversity and mindset, safety training and evolving practices. Identified behaviours include effective communication, commitment to safety, and the ability to inspire and motivate workers/crew towards safety-oriented goals, with participants stating that their understanding of safety leadership included such things as leading by example, being the sample of good safety onboard, and walking the walk. The study findings demonstrate that these results correlate with lower incident causation rates and an improved safety culture. The dissertation also highlights the vital role of leaders in setting safety standards, modelling positive safety behaviours and fostering a positive safety culture where safety is openly discussed, supported and addressed in a collaborative approach between workers and management. Additionally, participants identified barriers to effective safety leadership within the maritime environment, including operational pressures, time, money, cultural factors, and resistance to change. The study recommends overcoming challenges with training and implementing a proactive safety culture from the top down. In conclusion, this dissertation highlights the critically important role of behavioural- based safety leadership in ensuring a positive organisational safety culture while reducing incident causation rates in the high-risk maritime environment. It provides a pathway for maritime professionals to improve safety performance while suggesting a framework for future research into this vital area of social science.